الصعوبات التي تواجهها الموظفات المتزوجات في جامعة زاخو - عبدالله، ساجدة إسماعيل (المركز القومي للبحوث غزة, 2024)
يهدف البحث إلى التحقيق في الصعوبات التي تواجهها الموظفات المتزوجات في جامعة زاخو، وتقييم ما إذا كانت هناك اختلافات كبيرة في تجاربهن بناء على سنوات الزواج وتحديد مجالات الصعوبة الأساسية. مجتمع البحث، والموظفين في جميع الأقسام في كليات جامعة زاخو وبلغ عدد مجتمع البحث (309) في التركيز على الموظفين المتزوجين والبالغ عددهم (187). اعتمد هذا العمل على طريقة (العشوائية المتعمدة) لاختيار المجتمع البحثي للموظفات في جامعة زاخو في مختلف الكليات. وكانت أداة البحث عبارة عن مقياس جاهز السباعي (2004) للنساء العاملات. كما تكون المقياس بشكله النهائي على (32) فقرة موزعة على ثلاثة بدائل (دائما- أحيانا- أبدا). في حين استخدم الباحثان الأساليب الإحصائية مثل: اختبار "T" لعينة واحدة من أفراد عينة البحث واختبار T لعينتين مستقلتين من أفراد عينة البحث والوسط المرجح والانحراف المعياري لكل فقرة. وكشفت النتائج عن وجود صعوبات سائدة بين النساء العاملات، لا سيما في رعاية الأطفال، والرعاية الزوجية، والأعمال المنزلية، والأعباء الاجتماعية، والمسؤوليات الإدارية. وتختتم الدراسة بتوصيات تهدف إلى معالجة التحديات المحددة وتعزيز أنظمة الدعم للموظفات المتزوجات في جامعة زاخو. The research aimed to investigate the challenges faced by married female employees at the University of Zakho, assess whether there are significant differences in their experiences based on the years of marriage and identify the underlying areas of difficulty. The research community, employees in all departments in the faculties of the University of Zakho. The research community number was (309) in focusing on married employees which were (187). This work depended on (intentional randomness) method for selecting the research community of women employees at the University of Zakho in various faculties. The research tool was a ready-made scale Sibaay (2004) for employed women. Furthermore, the scale consisted in the final form on (32) items distributed on three alternatives (always- sometimes- never). Whereas the researchers used statistical methods such as: the “T” test for one sample of the members of the research sample and the T test for two independent samples of the research sample members, the weighted mean, and the standard deviation for each paragraph. The results revealed that there are difficulties prevalent among working women, particularly in childcare, spousal care, household chores, social burdens, and administrative responsibilities. The study concludes with recommendations aimed at addressing the identified challenges and strengthening support systems for married female employees at the University of Zakho.
Keywords: المرأة العاملة -- حقوق المرأة -- المشكلات الإدارية -- الجامعات العراقية